Renewable Energy Collaboration Potentials between Indonesia and Timor-Leste through the Lense of Nationally Determined Contributions (NDCs) - Anggraeni, Silvia Dian; Ramadhan, Iqbal; J. Abbas, Rusdi; Dunggio, Bianca Azallia; Anastasia, Salsabila Gracia (Prodi Hubungan Internasional Program Magister Univ. Muhammadiyah Yogyakarta, 2025)
This study investigates the untapped potential for South-South Cooperation (SSC) between Indonesia and Timor-Leste in the development of renewable energy. While both nations are endowed with energy resources and have aligned their policies with international sustainable development goals, cooperation in renewable energy is not maximally exploited. The study aims to identify the cooperation areas in the SSC context, particularly low-carbon development, in accordance with the Nations Determined Contributions (NDCs) of both countries. With a qualitative approach, the study combined primary and secondary data, which were presented in NDC reports. The study explored both countries' current energy scenarios, renewable energy development targets, and potential cooperative endeavors. The findings illustrate immense partnership opportunities driven by common and contrasting situations. Indonesia's advanced renewable energy sector places it in a position to support Timor-Leste technically, inducing a horizontal and non-conditioned SSC model. However, regulatory divergence, state coordination issues, and differential priorities ought to be addressed through composite coordination and care in managing government authority fragments. This research highlights the necessity of utilizing SSC to enhance renewable energy initiatives in the two countries to serve the goals of global sustainable development.